Performance of the CMS Zero Degree Calorimeters in pPb collisions at the LHC. (7th May 2021) - Surányi, O.; Al-Bataineh, A.; Bowen, J.; Cooper, S.; Csanád, M.; Hagopian, V.; Ingram, D.; Ferraioli, C.; Grassi, T.; Kellogg, R.; Laird, E.; Martinez, G.; et al.
Abstract: The two Zero Degree Calorimeters (ZDCs) of the CMS experiment are located at ± 140 m from the collision point and detect neutral particles in the |η| > 8.3 pseudorapidity region. This paper presents a study on the performance of the ZDC in the 2016 pPb run. The response of the detectors to ultrarelativistic neutrons is studied using in-depth Monte Carlo simulations. A method of signal extraction based on template fits is presented, along with a dedicated calibration procedure. A deconvolution technique for the correction of overlapping collision events is discussed.